Farming systems research finds a new image - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Farming systems research looks at agricultural production systems within the context of the ecological, social and economic environment experienced by the producer. In recent years agriculture in tropical countries has undergone many profound...